2008
DOI: 10.1097/ccm.0b013e318186a34a
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care unit mortality trends in children after hematopoietic stem cell transplantation: A meta-regression analysis*

Abstract: There is a widely held impression that intensive care unit mortality clearly decreased in children after hematopoietic stem cell transplantation. However, characteristics of intensive care unit admitted patients significantly changed over time. After correcting for this, an improvement in intensive care unit survival was less evident. More studies are needed before a true improvement in intensive care unit survival can be confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
2
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 50 publications
5
56
2
3
Order By: Relevance
“…3,13 Data suggesting that admission rates for HSCT patients have risen since the year 2000, 5 in conjunction with data showing that fewer HSCT patients have required mechanical ventilation since that time, support that trend in care. 6 Data obtained through the survey also suggest that there is variation in the approach to pediatric HSCT patients when they become critically ill. This variation applies to therapies provided both outside and within the PICU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,13 Data suggesting that admission rates for HSCT patients have risen since the year 2000, 5 in conjunction with data showing that fewer HSCT patients have required mechanical ventilation since that time, support that trend in care. 6 Data obtained through the survey also suggest that there is variation in the approach to pediatric HSCT patients when they become critically ill. This variation applies to therapies provided both outside and within the PICU.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Respiratory failure, secondary to pulmonary complications, is the most frequent reason for PICU admission, accounting for 35-88% of transfers. 2,4,5 Although debated, 6 several recent studies suggest improved survival over time in ventilated HSCT children with survival rates exceeding 50% being reported. 3,7,8 The reasons for this improvement have not been clearly established and are likely multifactorial.…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to the level of mortality found in a recent meta-analysis. 9 By comparison with many other studies that have suggested that invasive ventilation is a poor prognostic factor, 73% of PICU admission episodes that only required invasive ventilation resulted in survival to discharge. This is markedly higher than in historical series and reflects the results found in a more recent series of children undergoing HSCT for oncology diagnoses, which demonstrated improved survival over time for patients requiring ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis demonstrated an overall ICU mortality of 60% (ref. 9). However, there is debate as to whether there has been a decrease in mortality for HSCT recipients admitted to ICU over recent years, with some studies showing a marked increase in survival while others showed no change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation